Investigation of the Hydraulic Fracture Propagation Law of Layered Rock Strata Using the Discrete-Particle Model - Xin Zhang; Mei Yin (Geofluids)
Hydraulic fracturing is a rock structure transformation method that significantly weakens the mechanical properties of the hard roof strata. Considering the poor hydraulic fracturing effect of special structure such as composite layered rock, this paper carries out hydraulic fracturing numerical simulation experiments and compares the hydraulic fracture morphology and bedding plane interaction mode under different injection rate and injection modes. The experimental results show that the bedding plane can change the trajectory and propagation direction of hydraulic fracture. Under the low injection rate, hydraulic fracturing is conducive to open the bedding plane, but the expansion length of the main hydraulic fracture is easy to be limited. Under the high injection rate, the hydraulic fracture can extend for a long distance. But the fracture morphology tends to be slender and single, which is not conducive to the formation of fracture network. Compared with conventional hydraulic fracturing, stepped variable injection rate hydraulic fracturing can activate more bedding planes, so as to improve the effect of rock strata transformation. The experimental results are instructive in achieving effective control of composite layered rock.